Chlorophyll fluorescence of soybeans under the condition of drought generation - Hieu, Nguyen Van; Ma, Nguyen Van (Academia Journal of Biology, 2012)
We used the Chlorophyll fluorescence analysis method to study Chlorophyll of soybeans under the condition of drought generation. The result showed that the drought generation at the stage of blossom made the Fo of many researched soybean varieties increase. However, there was not any clear change in the variable fluorescence efficiency of almost strains. Particularly, the Fvm of DT12 decreased when lacking water. At the stage of tender nuts, the Fo of many strains was lower than that at the stage of blossom; however, this value in the experimental plot was higher than the comparative one and Fvm were equivalent in the two plots. Meanwhile, the Fvm of DT12 in the drought-generated plot was still clearly lower than in the comparative plot, which proved that this variety had not recovered its fluorescence ability after being generated drought. When being watered again, Fo of soybeans tended to reduce, Fm fluctuated wildly, not followed a certain direction and Fvm of almost strains tended to grow. The strains DT84 and AK06 are fairly good drought-resistant ones as they had quite stable fluorescence indexes in the drought generation and in the process of watering again after being withered.